PENGARUH LINGUNGAN KERJA, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN NON MEDIS RUMAH SAKIT RESTU IBU BALIKPAPAN - Khudin Anam, Sholih; Para’pak, Gebi; Yusuf, Tamzil (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This research aims to determine the influence of the work environment, work discipline, and motivation on employee job satisfaction at Restu Ibu Balikpapan Hospital. The population in this study was 352 employees of Restu Ibu Balikpapan Hospital. By using a purposive sampling technique, the sample used was 98 respondents. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to manage data. The results of this research indicate that the work environment variable has a positive and significant effect on the job satisfaction of employees at Restu Ibu Balikpapan Hospital. The Work Discipline variable has a positive and significant effect on the Job Satisfaction of Restu Ibu Balikpapan Hospital Employees. The motivation variable has a negative and insignificant effect on employee job satisfaction at Restu Ibu Balikpapan Hospital